Conflicted conservatives, punitive views, and anti-Black racial bias 1974–2014 - Brown, Elizabeth K. (Punishment & society, 2019)
Research suggests that the views of “conflicted conservatives,” Americans who self-identify as conservative but express support for liberal governmental policies and spending, are particularly important in policymaking and politics because they are politically engaged and often act as swing voters. We examine punitive views among conflicted conservatives and other political subgroups in three distinct periods in the politics of punishment in America between 1974 and 2014. In particular, we consider the punitive views of conflicted conservatives relative to consistent conservatives, moderates, and liberals. Given the barrier that racialized typifications of violent crime may pose to current criminal justice reform efforts, we also explore the role of anti-Black bias in predicting punitive views among White Americans across political subgroups. Our overall findings indicate that conflicted conservatives are like moderates in their support for the death penalty and like consistent conservatives on beliefs about court harshness. These findings, and supplemental analyses on punitive views and voting behaviors across political subgroups, call into question whether conflicted conservatives have acted as critical scorekeepers on penal policy issues. We also find that anti-Black racism was significantly related to punitive views across political subgroups and among liberals in particular.